Palaeolithic sites of Podillya (Ukraine) as geoheritage objects: key features and current challenges - Shevtsova, Anastasiia (Acta Geographica Lodziensia, 2024)
The article provides a comprehensive analysis of Palaeolithic sites as geoheritage objects. It also examines in detail the state of their preservation and the main problems related to the process of organising the protection of Palaeolithic heritage monuments in Ukraine (using the example of Palaeolithic sites in the Podillya region). The study focuses on the distinctive features of these geoheritage objects, emphasising their natural significance and unique historical features. Based on a detailed analysis of natural conditions, as well as legal aspects, this article presents ideas and best practices that can significantly change the Ukrainian approach to the preservation and management of Palaeolithic heritage. It highlights the importance of Palaeolithic sites as natural and cultural monuments that deserve our utmost care and attention.